Methods for Detecting and Measuring Adverse Hospital Events - A Baba-Akbari Sari; TA Sheldon (Tehran University of Medical Sciences, 2005)
Introduction: An adverse event is defined as an unexpected event such as a patient fall, a drug reaction or an infection, which leads to patient injury and is caused by healthcare management rather than patient own diseases. There is evidence to suggest that adverse events frequently occur in modern health systems. However, there is a lack of knowledge about the nature of adverse events and the performance of different methods to explore them. This survey is part of a PhD project, which aims to investigate the scale and nature of adverse events and compare different methods to identify them. The project has not been completed yet. The aim of this abstract is to explain the design and methodology of the project. Objectives: To explore the relative performance of two promising methods of medical record review (18 item and 8 item-screening criteria) for detecting adverse events and to compare this method with the routine hospital incident reporting system for detecting adverse events. Methods: A proportionate stratified random sample of 1000 patient records from Surgery, Medicine, Elderly, Orthopaedics and Urology specialties of a large UK hospital were selected and reviewed by nurses using a list of explicit criteria. Identification of one or more positive criteria was considered as an indicator of a potential adverse event. Doctors then reviewed these records in more depth and decided if there was an adverse event. If the doctor was fairly convinced that there was an adverse event, a structured review form was completed to explore the nature and likely causes of adverse event. We also check the hospital incident reporting systems to see if any adverse events were reported to the system about any of the patients in our sample. The data collection and analysis has not been completed yet. A preliminary analysis of the data showed that in 407(40.7% of) cases at least one criterion was recorded positive by the nurses. Positive criteria do not necessarily mean an adverse event; however, these cases are considered as potential for adverse events and are forwarded for further review by the doctors to check if there is any adverse event. This study has the potential to contribute to methods of research in this field, which will inform future quality improvement initiatives and contribute to future research.